2000
DOI: 10.1097/00005392-200010000-00008
|View full text |Cite
|
Sign up to set email alerts
|

FLEXIBLE URETEROSCOPES: A SINGLE CENTER EVALUATION OF THE DURABILITY AND FUNCTION OF THE NEW ENDOSCOPES SMALLER THAN 9Fr

Abstract: Small diameter flexible ureteroscopes are effective for diagnosing and treating upper urinary tract pathology but improved durability is required. Currently they represent a highly effective but high maintenance means of achieving retrograde access to the ureter and kidney with a need for repair after only 6 to 15 uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 10 publications
1
54
0
1
Order By: Relevance
“…Because of the miniaturization, these ureteroscopes are more fragile, especially regarding the deflection mechanism; this can result in high repair frequency and high operating costs. 2 Another problem is the loss of maximal deflection after introduction of stone management tools, which may prevent access to stones for disintegration. 3 Two new-generation ureteroscopes with an increased maximum angle of deflection beyond standard scope properties (Ͼ180°) have been developed: the Flex-X (Karl Storz, Tuttlingen, Germany) and the DUR-8 Elite (ACMI, Southborough, MA).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the miniaturization, these ureteroscopes are more fragile, especially regarding the deflection mechanism; this can result in high repair frequency and high operating costs. 2 Another problem is the loss of maximal deflection after introduction of stone management tools, which may prevent access to stones for disintegration. 3 Two new-generation ureteroscopes with an increased maximum angle of deflection beyond standard scope properties (Ͼ180°) have been developed: the Flex-X (Karl Storz, Tuttlingen, Germany) and the DUR-8 Elite (ACMI, Southborough, MA).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The quality of vision has essentially been focused on the arrival of liquid and not on lavage, which also includes suction. [8][9][10][11] The originality of the ENDO FMS UROLOGY system is based on the separation of the two main elements, pressure and flow regulation, which are independent.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a pressure of 400 mm Hg (543.8 cm H 2 O) was used as a maximum. 9 We therefore chose 300 mm Hg as the safety limit. No complications were registered with our pressurized technique although no intrarenal pressure measurements were taken.…”
Section: Technical Particularities Of Groups R1 and F1mentioning
confidence: 99%
“…White and Moran reported the need for major ureteroscope repairs after only 12 endoscope usages, while Afane et al demonstrated that flexible ureteroscopes from four major manufacturers required major repairs after only 15 procedures or 13 h of usage [28,29]. Traxer et al in Paris, with progressive surgical techniques, performed 50 complex flexible ureteroscopies with the Karl Storz Flex-X ureteroscope, the small diameter fiber optic flexible endoscope previously described.…”
Section: Ureteroscope Durabilitymentioning
confidence: 99%